An integrated approach to evaluate the hydrocarbon potential of Jurassic Samana Suk Formation in Middle Indus Basin, Pakistan - Muhammad Armaghan Faisal Miraj; Abid Ali; Hassan Javaid; Pal Washa S. Rathore; Naveed Ahsan; Rana F. Saleem; Sher Afgan; Muhammad B. Malik (Kuwait Journal of Science)
The Indus Basin is consider as prolific hydrocarbon bearing province of Pakistan. The study area lies in Middle Indus Basin, Pakistan, which is separated from Upper Indus Basin by Sargodha High. The research emphasizes on two-dimensional subsurface seismic interpretation of (Gojra block) and rock physics evaluation to estimate reservoir properties of Jurassic age i.e. Samana Suk Formation (Carbonate). Carbonate reservoirs have different heterogeneities including irregular distribution and porosity types making it difficult for reservoir estimation. Therefore, rock physics is vital in estimating reservoir properties using shear and compressional wave velocities. Data from nine 2-D seismic lines and two wells have been deliberated comprehensively. Five imperative reflectors were marked specifically (Salt Range Formation (Pre-Cambrian), Amb Formation (Permian), Samana Suk Formation (Jurassic), Dungan Formation (Paleocene) and of Eocene age and faults affecting the Paleozoic to Cenozoic strata in area. Time contour maps were constructed using seismic lines based on two-way travel time (TWT). The interpretive results from time contour maps indicate that most of the producing zones lie in north-westward direction at Jurassic level (Samana Suk Formation). The results also reveal that prospect zones tend to become thin in northeast, and thick in southwest. Rock physics interpretation of Samana Suk Formation indicates fair reservoir characterizations. As the results obtained from Poisons ratio, Bulk Modulus, Shear Modulus, Shear wave velocity, primary wave velocity, Vp/Vs ratio & Density model clearly shows presence of hydrocarbons in Samana Suk Formation level.